2022
DOI: 10.7717/peerj.13744
|View full text |Cite
|
Sign up to set email alerts
|

BMSC-derived exosomal miR-27a-3p and miR-196b-5p regulate bone remodeling in ovariectomized rats

Abstract: Background In the bone marrow microenvironment of postmenopausal osteoporosis (PMOP), bone marrow mesenchymal stem cell (BMSC)-derived exosomal miRNAs play an important role in bone formation and bone resorption, although the pathogenesis has yet to be clarified. Methods BMSC-derived exosomes from ovariectomized rats (OVX-Exo) and sham-operated rats (Sham-Exo) were co-cultured with bone marrow-derived macrophages to study their effects on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The use of hucMSC-EV has shown beneficial effects in a variety of diseases, such as lung disease ( Willis et al, 2020 ; Willis et al, 2021 ), oxygen-Induced multi-organ disease ( Fernandez-Gonzalez et al, 2021 ), preeclamptic lung Injury ( Taglauer et al, 2022 ), various detrimental sequalae of hyperoxia exposure ( Reis et al, 2021 ), cornea disease ( McKay et al, 2021 ), hepatic fibrosis ( Rong et al, 2019 ), etc. In rat calvarial defects, miR-196a ( Qin et al, 2016 ), miR-27a, and miR-206 ( Lai et al, 2022 ) positively regulate the expression of osteogenic genes and osteoblast differentiation to stimulate bone formation ( Liu et al, 2018 ). In a mouse model of Alzheimer’s disease, miR-21 and miR-181c effectively reduced amyloid-β accumulation and increased synaptic protein expression and miR-21 levels in the brains of APP/PS1 mice ( Cui et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of hucMSC-EV has shown beneficial effects in a variety of diseases, such as lung disease ( Willis et al, 2020 ; Willis et al, 2021 ), oxygen-Induced multi-organ disease ( Fernandez-Gonzalez et al, 2021 ), preeclamptic lung Injury ( Taglauer et al, 2022 ), various detrimental sequalae of hyperoxia exposure ( Reis et al, 2021 ), cornea disease ( McKay et al, 2021 ), hepatic fibrosis ( Rong et al, 2019 ), etc. In rat calvarial defects, miR-196a ( Qin et al, 2016 ), miR-27a, and miR-206 ( Lai et al, 2022 ) positively regulate the expression of osteogenic genes and osteoblast differentiation to stimulate bone formation ( Liu et al, 2018 ). In a mouse model of Alzheimer’s disease, miR-21 and miR-181c effectively reduced amyloid-β accumulation and increased synaptic protein expression and miR-21 levels in the brains of APP/PS1 mice ( Cui et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the anti‐osteogenic role of miR‐196b‐5p we observed contradicts a recently published article that reported an in vitro pro‐osteogenic effect of miR‐196b‐5p on rat BMSCs without investigating the underlying mechanism. ( 32 ) Although the exact reason remains unknown, the discrepancy may result from the different cellular context of different BMSCs between mouse and rat.…”
Section: Discussionmentioning
confidence: 99%
“…The formed axes either positively or negatively regulate many bone conditions. Lai et al showed that miR-27a-3p and miR-196b-5p help BMSCs differentiate into osteoblasts [ 68 ]. The miR-608/SP7 axis and circRNA hsa_circ_0001421/miR-608 partially control human adipose mesenchymal stem cell (hAMSC) osteoblastic differentiation, suggesting that hAMSCs can be used to treat osteoporosis [ 69 ].…”
Section: Other Ncrna-mediated Mir-124 Regulation Mechanisms In Bonementioning
confidence: 99%